2013
DOI: 10.1021/om400447q
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilicity of Neutral versus Cationic Magnesium Silyl Compounds

Abstract: Charge and ancillary ligands affect the reactivity of monomeric tris(trimethylsilyl)silyl magnesium compounds. Diamine-coordinated (tmeda)Mg{Si(SiMe3)3}Me (tmeda = tetramethylethylenediamine; 2-tmeda) and (dpe)Mg{Si(SiMe3)3}Me (dpe =1,2-N,N-dipyrrolidenylethane; 2-dpe) are synthesized by salt elimination reactions of L2MgMeBr and KSi(SiMe3)3. Compounds 2-tmeda or 2-dpe react with MeI or MeOTf to give MeSi(SiMe3)3 as the product of Si-C bond formation. In contrast, 2-tmeda and 2-dpe undergo exclusively reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The angles Si1–Mg1–O1 of 111.69(9)°, Si1–Mg1–O1′ of 105.92(9)°, and Si1–Mg1–Si1′ of 123.72(9)° indicate tetrahedral coordination geometry at the magnesium atom. The Mg1–Si1 bond length of 2.6737(15) Å compares to those in [Mg­(SiMe 3 )­Br­(TMEDA)] 2 (2.603(4) Å), [Mg­{Si­(SiMe 3 ) 3 } 2 ­(THF) 2 ] (2.682(2) Å), [Mg­{Si­(SiMe 3 ) 3 } 2 ­(TMEDA)] (2.708(3) Å), and [Mg­{Si­(SiMe 3 ) 3 }­Me­(TMEDA)] (2.6414­(9) Å) …”
Section: Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The angles Si1–Mg1–O1 of 111.69(9)°, Si1–Mg1–O1′ of 105.92(9)°, and Si1–Mg1–Si1′ of 123.72(9)° indicate tetrahedral coordination geometry at the magnesium atom. The Mg1–Si1 bond length of 2.6737(15) Å compares to those in [Mg­(SiMe 3 )­Br­(TMEDA)] 2 (2.603(4) Å), [Mg­{Si­(SiMe 3 ) 3 } 2 ­(THF) 2 ] (2.682(2) Å), [Mg­{Si­(SiMe 3 ) 3 } 2 ­(TMEDA)] (2.708(3) Å), and [Mg­{Si­(SiMe 3 ) 3 }­Me­(TMEDA)] (2.6414­(9) Å) …”
Section: Results and Discussionmentioning
confidence: 89%
“…The Mg1−Si1 bond length of 2.6737(15) Å compares to those in [Mg(SiMe 3 )Br(TMEDA)] 2 (2.603(4) Å), 15 [Mg{Si-(SiMe 3 ) 3 } 2 (THF) 2 ] (2.682(2) Å), 8 [Mg{Si(SiMe 3 ) 3 } 2 -(TMEDA)] (2.708(3) Å), 7 and [Mg{Si(SiMe 3 ) 3 }Me-(TMEDA)] (2.6414(9) Å). 21 [(Me 3 TACD)Mg(SiPh 3 )] (2) was synthesized from [Mg-(SiPh 3 ) 2 (THF) 2 ]•THF (1) and (Me 3 TACD)H in benzene at room temperature (rt) and was isolated as a colorless powder in 83% yield (Scheme 1). Complete removal of the byproduct triphenylsilane was only possible in benzene after a reaction time of 2 h. Triphenylsilane could not be fully separated by washing with n-pentane, if THF was used as the solvent or if the reaction time was not long enough.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction between L 2 Mg-MeBr and KSi(SiMe 3 ) 3 in benzene at room temperature for 4 h gave diamine coordinated (TMEDA)Mg[Si(SiMe 3 ) 3 ]Me 144 and (dpe)Mg[Si(SiMe 3 ) 3 ]Me 145 (Scheme 49). 135 Scheme 49 Synthesis of ligand-coordinated mixed silyl-Grignard…”
Section: Review Synthesismentioning
confidence: 99%
“…While much of this chemistry has historically focused on their use as stoichiometric reagents, more recent research has also begun to delineate a broadly based catalytic reactivity. In contrast, the chemistry of magnesium silanide reagents has attracted comparatively limited interest despite the clear utility of such species as sources of triorganosilyl anions. While Oestreich and co-workers have recently demonstrated that triorganosilylmagnesium halides are accessible by in situ oxidation of magnesium metal to MgBr 2 and lithium silanide transmetalation, , true silicon-centered Grignard analogues, which are prepared from elemental magnesium and a triorganosilyl halide, are limited to Ritter’s synthesis of Me 3 SiMgBr·L and Me 3 SiMgI·L (L = tetramethylethylenediamine or pentamethyldiethylenetriamine) . More commonly, the synthesis of silylmagnesium compounds has been achieved either by redox transmetalation of (R 3 Si) 2 Hg and magnesium or by salt metathesis between a sterically encumbered silylpotassium reagent and a magnesium halide. As part of a broader exploration of magnesium compounds in which the alkaline-earth metal is directly bonded to an element of group 13 or 14, we have previously reported that reaction of the β-diketiminato organomagnesium complex [(BDI)­MgBu] ( 1 ; BDI = HC­{(Me)­CN-Dipp} 2 , where Dipp = 2,6-diisopropylphenyl), with the silaborane Me 2 PhSi-Bpin provides facile access to the heteroleptic magnesium silanide [(BDI)­MgSiMe 2 Ph] ( 2 ; Scheme ). …”
Section: Introductionmentioning
confidence: 99%